Population Health Improvement: It’s Up to the Community—Not the Healthcare System - Deprez, Ron; Thomas, Rick (Maine Policy Review, 2016)
Despite the growing interest in population health on the part of health professionals, policy analysts, and government agencies, there is no widely accepted definition of the term nor agreement on how to apply the concept in health improvement planning. In this article, Ron Deprez and Rick Thomas clarify the definition, attributes, and applications of population health, tracing its history and evolution to its current form and assess the roles of communities and health systems in advancing a population health approach.